An Educational model of Creativity Enhancement in Design Studios Using Prior Researches - Behnam Kalantari (Space Ontology International Journal, 2020)
Despite a large body of research on creativity in architecture, the concept of creativity as a multi-faceted phenomenon in design studios is still challenging. The present study aims to analyze the related literature and systematically categorize them to provide a conceptual framework to enhance creativity in design studios. By using a qualitative researcher method along with Sandelowski and Barroso's seven-step meta-synthesis model, the researchers attempted to conduct a systematic study on the previous literature. 579 articles published between 1999 and 2020 were selected by the relevant keywords dealing with aspects of creativity and its role in design studios. Having reviewed the titles and abstracts of these articles, around 60 papers were selected for the final review. The results suggested that the conceptual elements of creativity, including person, environment, process, and product, are very significant in creativity enhancement in design studios but these factors alone cannot promote students' creativity. Therefore, other factors, such as instructional interventions in teaching creativity with the aid of creativity support tools, as well as a continuous assessment of creativity during the creative process, can be very helpful in promoting creativity. Consequently, it was found that the creativity enhancement elements in design studios can be classified into three main categories: conceptual framework, interventions, and assessment.